Effect of grinding on physicochemical properties of dietary fibre powder from pink guava by-products - Ibrahim, Aida Hamimi; A. S., Norhartini; I., Amin (Faculty of Engineering, Universiti Putra Malaysia, 2016)
This study was aimed to evaluate the effect of grinding on physicochemical properties of dietary fibre powder (DFP) from pink guava by-products for potential applications in foods. The DFP were divided into three groups of by-product which are refiner waste (RW), siever waste (SW) and decanter waste (DW). The studied samples were analysed for its particle size distribution, bulk density, water-retention capacity, oil-retention capacity, swelling capacity, and particle structures. For particle size distribution, the largest amount of DFP were retained on the 425 μm and 250 μm screen sizes except for RW where 66% of the particle size was more than 600 μm. For bulk density, all large-size particles of DFP showed lower density than small-size ones as smaller particles size would have a higher packing density due to the increase in porosity. The reduction in particle size resulted in increased hydration properties for SW and DW. On the other hand, a decrease in particle size of RW had decreased the ability of hydration properties. A similar trend of oil-retention capacity (ORC) of DFP was evident. ORC was found to increase with smaller particle size for SW and DW and no significant difference (p>0.05) for RW. The study of microstructures revealed that the grinding process resulted in the rupture of the hollow physical structure of fibre matrix and in a scale type structure, thereby providing increased surface area for water and oil absorption. As a result, DFP pink guava could be used not only for dietary fibre enrichment, but also as functional ingredients in many food products.